Dose–Response Relationship Between Serum 25(OH)D and the Risk of Abnormal Glycemic Status in Chinese Older Adults - Yuting Li; Jing Chen; Qingqing Man; Rui Wang; Deqian Mao; Min Li; Jian Zhang; Yichun Hu; Lichen Yang (Metabolites)
Background/Objectives: The relationship between serum 25-hydroxyvitaminD (25(OH)D) concentration and the risk of abnormal glycemic status remains contradictory. Whether sufficient 25(OH)D plays a role in reducing the risk of diabetes and prediabetes is debatable. Its dose–response relationship and the optimal 25(OH)D threshold are not clear. This study investigated the relationship between serum 25(OH)D and the risk of abnormal glycemic status to explore the optimal cut-off value. Methods: This study included 5856 Chinese older adults aged 60 years and above from the China Adult Chronic Disease and Nutrition Survey (CACDNS 2015–2017). Serum 25(OH)D concentration was measured via an enzyme-linked immuosorbent assay. Abnormal glycemic status in the present study includes diabetes and prediabetes. Statistical methods such as a locally weighted regression and smoothing scatterplot (LOESS), restricted cubic spline regression (RCS) and binary and trend logistic regression were used to explore the dose–response relationship and the optimal 25(OH)D threshold. Results: The concentration of 25(OH)D was nonlinearly related to the levels of FPG and HbA1C in the LOESS curves. The nonlinear relation between 25(OH)D and the risk of diabetes and prediabetes was illustrated in the RCS curves and the optimal 25(OH)D threshold beneficial for diabetes was preliminarily explored to be 29.06 ng/mL, but no threshold for prediabetes was found. The dose–response results showed that for each 1 ng/mL increase in 25(OH)D, the risk of the fasting glucose type of diabetes reduced by 2.1%, the risk of the abnormal HbA1C type of diabetes reduced by 2.2% and the risk of the mixed type of diabetes reduced by 1.7%, whereas a dose–response relationship was not found for prediabetes. Conclusions: Higher serum 25(OH)D concentrations in Chinese older adults were associated with a reduced risk of glycemic abnormalities. The optimal 25(OH)D cut-off value was sufficiently beneficial if the diseased diabetes risk was 29.06 ng/mL, but no threshold was found for prediabetes.